Dinamika psikologis remaja yang mengalami broken home karena orang tua bercerai - Mutmainnah Budiman; Widyastuti Widyastuti (Fakultas Psikologi, 2022)
Harmony in the family is something that every individual wants. However, there are some families who experience divorce due to conflict or dispute, so the term broken home was born. This study aims to examine the experiences and meanings of adolescents on the condition of a broken home experienced because their parents divorced. The research was conducted using a qualitative method with a phenomenological approach. The research respondents were taken through purposive sampling technique, totaling three people aged 15-21 years with divorced parents. Data obtained from interviews were then analyzed using Interpretative Phenomenological Analysis. The results of the analysis of this study indicate that the three respondents experienced changes in behavior in a negative direction, uncontrollable emotions, and psychological conditions with trauma. In addition, they said that their parents paid less attention and affection after the divorce. As for their positive meaning of parental divorce as a process of self-maturation, besides being interpreted negatively as a dark period and the lowest point in life. Keywords: adolescents, broken home, family, psychological